Development of thermo-regulating fabrics with enhanced heat dissipation via graphene-modified n-octadecane microcapsules - Hiçyılmaz, Ayşe Sezer; Teke, Sengul; Islek Cin, Zeynep; Bedeloğlu, Ayşe (Wiley, 2021)
Phase change materials (PCMs) are of great importance in thermal regulation applications, but low thermal conductivity is the most critical disadvantage of these materials. Especially in the textile field, while there are many studies on the production of PCM-coated fabrics, studies on improving heat dissipation are quite limited. Therefore, in this study, first, n-octadecane was encapsulated with melamine formaldehyde shell modified with graphene as a thermal conductivity enhancer, and then, synthesized PCM microcapsules were coated on polyester fabrics. Chemical, morphological, thermal properties, as well as phase change behavior of microcapsules and coated fabrics were analyzed. The thermal conductivity of the PCM microcapsule-coated PET fabrics was increased by 31% with the addition of very low amount of graphene (0.1%).
Keywords: graphene; microcapsule; n-octadecane; phase change materials; polyester fabric; thermal conductivity